She Wolf by Isla Cowan - Yavuz Pala (Theatre Academy)
This paper analyses She Wolf (2022) by the contemporary British playwright, Isla Cowan, regarding ecofeminism and cultural politics. The paper also examines the relations between women and the environment in culture, politics and economy in terms of ecofeminism.